ROAD ROUGHNESS MEASUREMENT: COMPARISON OF TWO METHODS, MERLIN AND THE BUMP INTEGRATO - Jonathan Adhitya, Alvin
ROAD ROUGHNESS MEASUREMENT: COMPARISON OF TWO METHODS, MERLIN AND THE BUMP INTEGRATOR, Adhitya, Alvin Jonathan, 1989, Program Sistem dan Teknik Jalan Raya, Fakultas Pasca Sarjana, Institut Teknologi Bandung. Measurement of roughness of pavement surface is important to assess performance, and enable decisions as to what level of maintenance may require to be applied to the pavement in order to improve its serviceability and reduce vehicle operating costs. Measurement of pavement roughness is also useful in determining pavement adequacy for safety, and possibly for evaluating pavement distress. A new device for measuring roughness called MERLIN was first introduced in 1986, a Machine for Evaluating Roughness using Low-cost INstrumentation. This device is a simple, low-cost and easy-to-use means of measuring pavement roughness, and was design for use particularly in developing countries. Unlike the well established Bump Integrator, MERLIN does not measure roughness continuously, but at predetermined regular intervals. A series of trials on different types and conditions of road surfaces using both a MERLIN and a Bump Integrator were carried out. Comparison of the results obtained has shown that measuring roughness with a MERLIN is very practicable and one run of a MERLIN with one measurement taken at every seven wheel revolutions, over a 450 m length of test section, is adequate for estimating with sufficient accuracy the Bump Integrator irregularity index within the range 1000 to 5500 mm/km (International Roughness Index range 1.5 to 6.8 m/km). The work described in this thesis must be regarded as preliminary; considerable further effort is required to generalize the results obtained